2019
DOI: 10.3390/cancers11060879
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Albumin, Bilirubin, and ALBI Scores: Analysis of 1000 Patients with Hepatocellular Carcinoma Undergoing Radioembolization

Abstract: Introduction: We compared the efficacy of the ALBI (albumin–bilirubin) score to the established Child–Pugh (CP) grade in hepatocellular carcinoma (HCC) patients treated with yttrium-90 radioembolization (Y90). We further assessed the individual contributions of albumin and bilirubin to survival prediction. Methods: 1000 consecutive HCC patients treated with Y90 were included. Overall survival (OS) was assessed using Kaplan Meier analysis. Sub-stratification analyses were performed using CP and ALBI and in subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 18 publications
5
46
0
Order By: Relevance
“…16 The ALBI score uses albumin and bilirubin levels to show liver damage, and it has been confirmed to be a useful score in reflecting the prognosis of hepatocellular carcinoma. 17 Our data showed that the ALBI score and CLIF-SOFA score had similar efficacy in assessing the prognosis of ACLF patients. One single-center study indicated that the ALBI score was more effective and accurate than Child-Pugh and MELD scores in predicting the longterm prognosis for HBV-ACLF.…”
Section: Dovepresssupporting
confidence: 58%
“…16 The ALBI score uses albumin and bilirubin levels to show liver damage, and it has been confirmed to be a useful score in reflecting the prognosis of hepatocellular carcinoma. 17 Our data showed that the ALBI score and CLIF-SOFA score had similar efficacy in assessing the prognosis of ACLF patients. One single-center study indicated that the ALBI score was more effective and accurate than Child-Pugh and MELD scores in predicting the longterm prognosis for HBV-ACLF.…”
Section: Dovepresssupporting
confidence: 58%
“…Additionally, there are various prognostic parameters which involve albumin in itself such as albumin-globulin, albuminfibrinogen, albumin-bilirubin, prognostic nutritional index. Previous studies established the association of low levels of all these parameters with poor prognosis (22)(23)(24)(25)(26). Taken together, these results establish the prognostic value of albumin either alone or combined with different parameters.…”
Section: Discussionsupporting
confidence: 67%
“…For instance, tumor necrosis factor-α and IL-6 inhibit the synthesis of albumin, causing hypoalbuminemia [25]. Present studies have indicated that hyperfibrinogenemia was significantly correlated with shorter OS in patients with advanced PC and hypoalbuminemia is negatively correlated with prognosis in patients with hepatocellular carcinoma and diffuse large B-cell lymphoma [26][27][28]. Based on the above studies, researchers were keen to explore whether FAR was also associated with prognosis.…”
mentioning
confidence: 99%